Strategies to Improve the Competence of the Head of Administrative Affairs in Improving Performance in the Police General Planning and Budget Staff Environment - Muhammad Nur Rohman Taufik; Bambang Giyanto; Asropi Asropi (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to identify the factors that cause the suboptimal competence of the Head of Administrative Affairs, so as to provide a better understanding in improving performance in the Police General Planning and Budget Staff environment, as well as to determine the right strategy in improving the competence of the Head of Administrative Affairs in the Police General Planning and Budget Staff environment. The research method used in this research is descriptive research method with qualitative approach. The results of this study indicate that the strategy of renewal attitude, compliance attitude, collaboration attitude illustrates Kaurmin's commitment to continuously assess and improve performance through a critical and data-based approach. Through a policy-leading attitude and a collaborative attitude that strengthens teamwork, Kaurmin can ensure that the planning and budget process not only complies with the rules, but is also enriched by joint contributions, creating an efficient, effective and change-responsive environment that supports the planning and budget objectives of the Police Planning and Budget Staff. The importance of the Chief Administrative Officer's knowledge of planning technology, police regulations, related innovations, performance indicators and monitoring, and digital collaboration, in the context of planning and budgeting within the Police Planning and Budget Staff is significant. This study found that there is a need for a strategy to improve several specific skills in the context of improving the performance of the Head of Administrative Affairs in the Police Planning and Budget Staff, namely with Expertise in in-depth understanding of policies and regulations, providing a solid foundation for preparing plans and budgets in accordance with the applicable legal framework. Skills in analyzing needs and strategic plans are the focus, where analytical skills are an important asset in identifying opportunities, overcoming challenges, and formulating strategic steps.